Preparation method and application of recoverable La (OH) 3 / Fe3C ordered mesoporous carbon electrode
By preparing La(OH)3/Fe3C ordered mesoporous carbon electrodes with high selectivity and strong cycle stability, the existing technical problems of nitrogen and phosphorus pollutants removal in water bodies were solved, and efficient and environmentally friendly electrochemical nitrogen removal was achieved. Phosphorus removal effect and improves the recyclability of the material.
Patent Information
- Application Number
- CN202411441145.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-14
AI Technical Summary
In the prior art, when removing nitrogen and phosphorus pollutants in water, chemicals are used in large quantities, complex operating steps and low recyclability, and synchronous removal of nitrogen and phosphorus is difficult to achieve high efficiency, especially in the preparation of dual-containing La(OH)3 and Fe3C. Mesoporous materials of the active components have not been reported.
Ferulic acid, F127 and ferric nitrate as raw materials, and the La(OH)3/Fe3C ordered mesoporous carbon electrode with high selectivity and strong cycle stability was prepared by solvent volatilization-induced self-assembly method and impregnation method for electrochemistry. Nitrogenation and phosphorus removal reaction.
In a wide pH range and complex ionic environment, efficient nitrogen and phosphorus removal is achieved, material selectivity and stability are significantly improved, pollution risk is reduced, and electrode materials are recyclable.
Smart Images

Figure CN119306221A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of preparation methods of mesoporous carbon electrodes, and in particular relates to a preparation method and application of a recyclable La(OH)3 / Fe3C ordered mesoporous carbon electrode. Background Art
[0002] Nitrogen and phosphorus are essential elements for the growth and development of plants and animals. However, excessive nitrogen and phosphorus content in natural water bodies will cause environmental problems such as eutrophication of water bodies. Increasing the intake of phosphorus and nitrates by the human body increases the risk of human disease, thereby endangering human health. Therefore, most countries have strict standards for the content of nitrogen and phosphorus in water bodies. In addition, nitrogen and phosphorus often appear at the same time in natural water bodies. Therefore, removing only one substance (nitrogen or phosphorus) cannot effectively inhibit the eutrophication of water bodies. At present, the simultaneous removal of nitrogen and phosphorus pollutants in water bodies is a hot issue for the control of actual water eutrophication and water treatment.
[0003] In order to adapt to the increasingly perfect wastewater discharge laws and regulations. Currently, many chemical, adsorption, biological methods or a combination of these methods are used in wastewater treatment to reduce the nitrogen and phosphorus content in the water. However, these methods still have a lot of room for improvement in application, such as: large amount of chemicals used, complex operating steps, and low recyclability. Electrochemical denitrification and phosphorus removal has low reaction requirements, high efficiency, and low pollution risk, and is considered to be a new and efficient strategy.
[0004] Transition metals (Fe, Cu, Ni, etc.) are widely used in the study of electrochemical nitrogen and phosphorus pollutants due to their low cost, good conductivity, and high conversion efficiency. Transition metal-doped electrode materials can reduce nitrates to ammonium or nitrogen in water samples. As a nitrate electrocatalytic material, the study of Fe3C has been widely recognized and has great development potential. La(OH)3 has a strong affinity for phosphorus, so it can selectively bond with phosphate in a high-speed diffusion system. However, the binding of phosphate requires sufficient space gaps to improve the catalytic efficiency. Therefore, a moderate void structure on the surface of the material is very necessary. Ordered mesoporous carbon materials not only provide sufficient adsorption gaps for phosphates, but also reduce the resistance of interfacial electron transfer during nitrate reduction. According to the materials we collected, so far, the preparation of mesoporous materials containing La(OH)3 and Fe3C dual active components as electrode materials for simultaneous denitrification and dephosphorization has never been reported. Summary of the invention
[0005] The invention adopts ferulic acid, F127 and ferric nitrate as raw materials to prepare an ordered mesoporous carbon material with high selectivity, low precipitation formation rate and strong cycle stability, and can efficiently remove nitrogen and phosphorus in a wide pH range and complex ion environment.
[0006] A method for preparing a recyclable La(OH)3 / Fe3C ordered mesoporous carbon electrode comprises the following steps:
[0007] 1) 0.5 g of ferulic acid was dissolved in 60 mL of acetone to prepare solution A, 1 g of F127 was dissolved in 20 mL of acetone to prepare solution B, and 0.5 g of ferric nitrate nonahydrate was dissolved in 5 mL of acetone to prepare solution C.
[0008] 2) Add solution A to solution B and stir continuously for 30 minutes. Slowly add solution C to the above mixed solution AB and continue stirring for 30 minutes. Transfer solution ABC to a polytetrafluoroethylene dish and place it at room temperature 25°C for 12 hours to evaporate the solvent.
[0009] 3) The sample was placed in an oven at 100°C for thermal crosslinking for 24 hours. The crosslinked brown flaky solid was placed in a tube furnace, heated to 800°C and calcined for 2 hours under a nitrogen atmosphere to obtain the product OMC-Fe3C.
[0010] 4) Dissolve LaCl3·7H2O or lanthanum nitrate in 50 mL of water-ethanol mixture.
[0011] 5) Add 1 g OMC-Fe3C to the above mixture, add 1 M NaOH solution dropwise, and adjust the pH value to 10.
[0012] 6) Stir at 60°C for 2 h, and continue stirring at room temperature (25°C) for 24 h.
[0013] 7) Finally, the solid sample was separated by centrifugation, washed with deionized water until the pH was neutral, and dried under vacuum at 60°C for 24 h to obtain sample Y-La#OMC-Fe3C, where Y represents the amount of LaCl3·7H2O in mmol.
[0014] Furthermore, in step 3), the temperature is raised to 800° C. at a heating rate of 1° C. / min under a nitrogen atmosphere.
[0015] Further, in step 4), the amount of LaCl3·7H2O or lanthanum nitrate added is 2.5-10 mmol. Preferably, the amount of LaCl3·7H2O or lanthanum nitrate added is 2.5, 5, 7.5, 10 mmol.
[0016] Furthermore, in the water-ethanol mixed solution of step 4), V water:V ethanol=80 / 20.
[0017] Further, in step 6), after stirring, ensure that all La 3+ Converted into La(OH)3 and dispersed into the ordered mesopores.
[0018] The present invention also provides the application of the recyclable La(OH)3 / Fe3C ordered mesoporous carbon electrode prepared by the above method, and the electrode is used for the reduction reaction of electrochemical denitrification and dephosphorization.
[0019] The technical effects of the present invention are:
[0020] The present invention provides a method for preparing recyclable La(OH)3 / Fe3C ordered mesoporous carbon. The method uses a combination of solvent evaporation induced self-assembly (EISA) and impregnation to prepare an ordered mesoporous carbon electrode material containing La(OH)3 and Fe3C dual active components. The material has high selectivity, strong cycle stability, and low precipitation formation rate. The electrode material can maintain excellent performance in a wide pH range and complex ion environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 .TEM images of La#OMC-Fe3C materials (a) 2.5-La#OMC-Fe3C; (b) 5-La#OMCFe3C; (c) 7.5-La#OMC-Fe3C; (d) 10-La#OMC-Fe3C; (e) STEM image of 7.5-La#OMC-Fe3C and (f) element distribution map of C (g) O (h) Fe (i) La.
[0022] Figure 2 .Surface properties and characteristics of OMC-Fe3C and Y-La#OMC-Fe3C materials (a) nitrogen adsorption-desorption isotherms and (b) pore size distribution.
[0023] Figure 3 .Analysis of La#OMC-Fe3C electrode material before and after electrochemical denitrification and dephosphorization (a) FTIR spectrum; (b) P 2p XPS spectrum; c) La 3d XPS spectrum; d) Fe 2p XPS spectrum. Reaction conditions: 20 mg / L NO3 - -N, 2mg / L H2PO4 - -P, 0.1M Na2SO4, 0.02M NaCl; 25°C, pH=7).
[0024] Figure 4 .Y-La#OMC-Fe3C electrochemical simultaneous removal of nitrogen and phosphorus (reaction conditions: 50mg / L NO3 — N, 5mg / L H2PO4 - -P, 0.1M Na2SO4, 0.02M NaCl, -1.5V (vs SCE), 25°C, pH=7, 24h).
[0025] Figure 5.Relationship between electrochemical removal of nitrogen and phosphorus by La#OMC-Fe3C and reaction time (a) Nitrate removal performance and nitrogen selectivity; (b) Intermediate product concentration at different times; (c) Phosphorus removal capacity and removal rate and (d) Phosphorus concentration (reaction conditions: 50 mg / L NO3 - -N, 5mg / L H2PO4 - -P, 0.1M Na2SO4, 0.02M NaCl; 1.5V (vs SCE), 25°C, pH=7, 24h).
[0026] Figure 6 Effect of different pH values on simultaneous removal of nitrogen and phosphorus by La#OMC-Fe3C electrode (a) Nitrogen removal and N2 selectivity; b) Phosphorus removal and changes in electrolyte pH before and after reaction; Reaction conditions: 50 mg / L NO3 - N, 5mg / L H2PO4 - -P, 0.1M Na2SO4, 0.02M NaCl; -1.5V (vs SCE), 25℃, 24h).
[0027] Figure 7 .La#OMC-Fe3C electrode for simultaneous nitrate and phosphate removal in solutions containing additional ions that affect performance (a) Nitrate removal and Cl - concentration; (b) The relationship between the concentration of each ion and Cl after the electrochemical reaction - concentration; (c) Phosphate removal and Ca 2+ concentration and (d) nitrate removal with Ca 2+ concentration relationship (reaction conditions: 0.1 M Na2SO4, 0.02 M NaCl; -1.5 V (vs SCE), 25°C, pH = 7).
[0028] Figure 8 .La#OMC-Fe3C electrode phosphorus removal performance and Cl - The relationship between concentration. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is described in detail below with reference to the accompanying drawings.
[0030] Dissolve 0.5g of ferulic acid in 60mL of acetone to prepare solution A, dissolve 1g of F127 in 20mL of acetone to prepare solution B, and dissolve 0.5g of ferric nitrate nonahydrate in 5mL of acetone to prepare solution C. Add solution A dropwise to solution B and stir continuously for 30min. Slowly add solution C dropwise to the above AB mixed solution and continue stirring for 30min. Transfer solution ABC to a polytetrafluoroethylene dish and place it at room temperature (25°C) for 12h to evaporate the solvent. Place the sample in an oven at 100°C for thermal crosslinking for 24h. Place the crosslinked brown flaky solid in a tubular furnace and heat it to 800°C at a rate of 1°C / min in a nitrogen atmosphere for calcination for 2h to obtain the product OMC-Fe3C.
[0031] Different amounts (2.5, 5, 7.5, 10 mmol) of LaCl3·7H2O were dissolved in 50 mL of a water-ethanol mixture (V water: V ethanol = 80 / 20). 1 g of OMC-Fe3C was added to the mixture, and 1 M NaOH solution was added dropwise to adjust the pH value to 10. Stir at 60 °C for 2 h, and continue stirring at room temperature 25 °C for 24 h to ensure that all La 3+ The solid sample was centrifuged and washed with deionized water until the pH was neutral. The sample was dried at 60 °C in vacuum for 24 h to obtain the sample Y-La#OMC-Fe3C, where Y represents the amount of LaCl3·7H2O (in mmol).
[0032] Table 1: Physical and chemical properties of Y-La#OMC-Fe3C samples
[0033]
[0034] like Figure 1 The TEM image of La#OMC-Fe3C is shown in Figure 1. The material has a clear and ordered mesoporous structure, which is conducive to the transfer of electrons and the adsorption of phosphates. The N2 adsorption-desorption curve of La#OMC-Fe3C shows a typical IV type isotherm ( Figure 2 a), H1 type hysteresis loop appears in the range of P / P0=0.4-0.8, indicating the formation of mesoporous structure. The pore size distribution of La#OMC-Fe3C material is concentrated in two regions (1.1~1.2nm) and (4.9~5.1nm) ( Figure 2 b). In terms of chemical composition, La#OMC-Fe3C is mainly composed of four elements: C, O, Fe, and La. In 7.5-La#OMC-Fe3C, the contents of Fe and La are 12.7% and 29.7% respectively. As shown in the element distribution diagram ( Figure 1 fi), C, O, Fe and La are uniformly dispersed in 7.5-La#OMC-Fe3C.
[0035] Figure 3 a shows the FTIR spectra of La#OMC-Fe3C before and after dephosphorization in the electrochemical system. Before the reaction, La#OMC-Fe3C has a peak at 1571 cm -1 and 3541cm -1 After the reaction, the -OH stretching vibration peak weakened and the peak at 612 cm -1 and 1054cm -1 New stretching vibration peaks appeared, which were related to PO and OPO.
[0036] like Figure 3 b, 3c, 3d, in the XPS analysis of La#OMC-Fe3C ( Figure 3 b), after the reaction, a peak of P appeared, indicating that P was mainly in the form of H2PO4 - and HPO4 2- The La XPS pattern after the reaction was found to have a significant blue shift ( Figure 3 c) Detection of La3d 3 / 2 and La3d 5 / 2 The binding energy of La#OMC-Fe3C increased by about 0.6 eV. This should be because La-OP affects the electron transfer of La in the valence band, which indicates that phosphate is mainly fixed on La(OH)3. There is no obvious change in the XPS spectrum of Fe in the La#OMC-Fe3C electrode before and after the reaction ( Figure 3 d), which indicates that the valence state of Fe remains unchanged before and after the electrode reaction, and Fe3C can continuously provide electrons for nitrate reduction.
[0037] Example 1
[0038] Materials (Y-La#OMC-Fe3C) with different La loadings (2.5, 5, 7.5, 10 mmol) were prepared by using different amounts of LaCl3·7H2O. - -N, 5mg / L H2PO4-P, 0.1MNa2SO4, 0.02MNaCl system for electrochemical nitrogen and phosphorus removal. The reaction was carried out at -1.5V (vs SCE) for 24h, and the water sample was filtered and the nitrate nitrogen (NO3 - -N) and phosphorus concentration.
[0039] See attached Figure 4Figure a shows that the nitrate removal capacity of OMC-Fe3C is 150 mg N / gFe when the La loading is 0. When the La loading increases from 2.5 mmol to 10 mmol, the nitrate removal increases from 155.5 mg N / g Fe to 256.2 mg N / g Fe.
[0040] See attached Figure 4 As shown in Figure b, when the material is not loaded with La, OMC-Fe3C cannot remove phosphate from water. When the La loading reaches 7.5mmol, the phosphorus removal effect of Y-La#OMC-Fe3C increases to 93.8%. Generally, as the La loading increases, the phosphorus removal effect of Y-La#OMC-Fe3C increases. When the La loading increases to 10mmol, the phosphorus removal effect of 10-La#OMC-Fe3C decreases to 91.6%.
[0041] Example 2
[0042] For the experiment of denitrification and phosphorus removal of La#OMC-Fe3C with different reaction times, the La#OMC-Fe3C electrode was placed in an aqueous solution (50 mg / L NO3 - -N, 5mg / L H2PO4-P, 0.1M Na2SO4, 0.02MNaCl) were reacted (25°C, pH=7). The test was divided into 6 groups, and the reaction time was 2h, 4h, 8h, 12h, 16, and 24h respectively. After the reaction, the mixture was filtered and the nitrate nitrogen and phosphorus concentrations in the filtrate were measured.
[0043] Figure 5 The relationship between the electrochemical removal of nitrogen and phosphorus by La#OMC-Fe3C and the reaction time is given, including: (a) nitrate denitrification performance and nitrogen selectivity; (b) the concentration of intermediate products at different times; (c) phosphorus removal capacity and removal rate and (d) phosphorus concentration. It can be seen that with the increase of reaction time, the denitrification and phosphorus removal effect of La#OMC-Fe3C is enhanced. After 2h of reaction, the phosphorus removal amount of La#OMC-Fe3C is 7.96mg P / g La. When the reaction reaches 4h, the nitrogen removal amount of La#OMC-Fe3C reaches 221mg N / g Fe. After 24h of reaction, the nitrate nitrogen removal rate reaches 88.3%, and the phosphorus removal rate reaches 93.8%.
[0044] Example 3
[0045] To determine the effect of La#OMC-Fe3C in the simultaneous removal of nitrogen and phosphorus in different pH systems, La#OMC-Fe3C was added to the mixed solutions with pH values of 3, 7, and 11 (50 mg / L NO3 --N, 5mg / L H2PO4-P, 0.1M Na2SO4, 0.02MNaCl). The mixture was reacted at 25°C for 24h. After filtration, the concentrations of nitrate nitrogen and P were measured.
[0046] Depend on Figure 6 It can be seen that with the increase of pH value, the removal efficiency of La#OMC-Fe3C electrode for nitrate and phosphorus shows a downward trend. When pH=3, the removal efficiency of the two is 92.5% and 98.2% respectively. When pH=7, the two are 87% and 94.2% respectively. When pH=11, the two are 82.2% and 79.9% respectively.
[0047] Example 4
[0048] To determine the effect of interfering ions on simultaneous nitrogen and phosphorus removal, electrochemical simultaneous removal of SO4 was performed from real seawater using La#OMC-Fe3C electrodes in the presence of electrolytes. 2- 、Na + , K + The presence of has little effect on the denitrification and phosphorus removal of La#OMC-Fe3C electrode.
[0049] Table 2 Concentrations of substances before and after electrochemical removal of nitrogen and phosphorus from real seawater by La#OMC-Fe3C electrode in the presence of electrolyte
[0050]
[0051] See attached Figure 7 and attached Figure 8 The effects of four chloride ion concentrations, 0, 0.002, 0.02, and 0.2 M, on the denitrification and phosphorus removal efficiency of La#OMC-Fe3C electrode were compared. - With the increase of concentration, the denitrification capacity of La#OMC-Fe3C electrode increased from 235mgN / gFe to 283mgN / gFe. When the chloride ion concentration reached 0.2M, the N2 selectivity was 100%. The chloride ion concentration of the solution had almost no effect on the removal of phosphate.
[0052] When the initial phosphorus concentration was 5 mg / L, the phosphorus removal efficiency of La#OMC-Fe3C electrode was 93.8%. 20 mg / L Ca 2+ or Mg 2+ , the phosphorus removal rates were 98.2% and 100% respectively. The initial phosphorus concentration in the solution was increased to 30 mg / L, and Ca was added to the solution. 2+ , the concentrations were 20mg / L and 70mg / L respectively. The phosphorus removal effects were 2+In the system of 0.1M Na2SO4, 0.02M NaCl; -1.5V (vs SCE), 25℃, pH=7, Ca 2+ The concentrations were 0, 20, 70, and 120 mg / L, respectively, and the removal of nitrate nitrogen by the La#OMC-Fe3C electrode was not adversely affected.
[0053] Example 5
[0054] Due to the complexity of the components contained in the actual water environment. In order to investigate the application of La#OMC-Fe3C electrode in actual water samples, seawater (specific conductivity = 28.1ms / cm) was collected from the Yellow Sea area of the Navy Park in Qingdao, Shandong. NaNO3 and NaH2PO4 were added to the solution to adjust the initial concentrations of N and P to 50mg / L and 5mg / L, respectively.
[0055] As can be seen from Table 3, the removal efficiency of La#OMC-Fe3C electrode for nitrate nitrogen in actual seawater is 89.9%, and the removal efficiency of phosphorus is 100%. This result further proves that La#OMC-Fe3C has great application potential in removing actual nitrogen and phosphorus water samples.
[0056] Table 3 Species concentrations before and after electrochemical removal of nitrogen and phosphorus in actual seawater by La#OMC-Fe3C electrode
[0057]
[0058] It should be further explained that the above implementation modes are only used to understand the technical solutions of the present invention, and are not intended to limit the protection scope of the present invention. Any obvious adjustments and modifications to the technical concepts and implementation modes of the present invention should also fall within the protection scope of the present invention.
Claims
1. A method for preparing a recyclable La(OH)3 / Fe3C ordered mesoporous carbon electrode, characterized in that The following steps are involved: 1) 0.5 g of ferulic acid was dissolved in 60 mL of acetone to prepare solution A, 1 g of F127 was dissolved in 20 mL of acetone to prepare solution B, and 0.5 g of ferric nitrate nonahydrate was dissolved in 5 mL of acetone to prepare solution C. 2) Add solution A to solution B and stir continuously for 30 minutes. Slowly add solution C to the above mixed solution AB and continue stirring for 30 minutes. Transfer solution ABC to a polytetrafluoroethylene dish and place it at room temperature 25°C for 12 hours to evaporate the solvent. 3) The sample was placed in an oven at 100°C for thermal crosslinking for 24 hours. The crosslinked brown flaky solid was placed in a tube furnace, heated to 800°C and calcined for 2 hours under a nitrogen atmosphere to obtain the product OMC-Fe3C. 4) Dissolve LaCl3·7H2O or lanthanum nitrate in 50 mL of water-ethanol mixture. 5) Add 1 g OMC-Fe3C to the above mixture, add 1 M NaOH solution dropwise, and adjust the pH value to 10. 6) Stir at 60°C for 2 h, and continue stirring at room temperature (25°C) for 24 h. 7) Finally, the solid sample was separated by centrifugation, washed with deionized water until the pH was neutral, and dried under vacuum at 60°C for 24 h to obtain sample Y-La#OMC-Fe3C, where Y represents the amount of LaCl3·7H2O in mmol.
2. The method for preparing the recyclable La(OH)3 / Fe3C ordered mesoporous carbon electrode according to claim 1, characterized in that: In step 3), the temperature is raised to 800° C. at a heating rate of 1° C. / min in a nitrogen atmosphere.
3. The method for preparing the recyclable La(OH)3 / Fe3C ordered mesoporous carbon electrode according to claim 1, characterized in that: In step 4), the amount of LaCl3·7H2O or lanthanum nitrate added is 2.5-10 mmol.
4. The method for preparing the recyclable La(OH)3 / Fe3C ordered mesoporous carbon electrode according to claim 1, characterized in that: In step 4), the amount of LaCl3·7H2O or lanthanum nitrate added is 2.5, 5, 7.5, 10 mmol.
5. The method for preparing the recyclable La(OH)3 / Fe3C ordered mesoporous carbon electrode according to claim 1, characterized in that: In the water-ethanol mixed solution of step 4), V water:V ethanol=80 / 20.
6. The method for preparing the recyclable La(OH)3 / Fe3C ordered mesoporous carbon electrode according to claim 1, characterized in that: In step 6), after stirring, ensure that all La 3+ Converted into La(OH)3 and dispersed into the ordered mesopores.
7. Application of the recyclable La(OH)3 / Fe3C ordered mesoporous carbon electrode prepared by the method according to any one of claims 1 to 6, characterized in that: Used for reduction reaction of electrochemical denitrification and phosphorus removal.
Citation Information
Patent Citations
Preparation method and application of nitrogen-doped ordered mesoporous carbon electrode
CN112850860A
AU2013206605A1